The Mechanics of Opera Ballet Philippines X Gabby Barredo - Morales, Paul Alexander (2023)
This paper essays the circumstances and events that came into consonance to create Ballet Philippines' landmark collaboration with acclaimed Filipino artist Gabby Barredo. The idea of an evening length, multimedia dance production was borne as an expansion of Barredo's installation, also called Opera, that was first presented at the Art Fair Philippines in 2013. In my first-hand account as former artistic director of Ballet Philippines, and producer of Opera, we retrace the symphony of interconnections that had led, three years later in 2016, to its actualization - a fusion of dance and contemporary sculptural art.

As a remembrance, in view of Gabby's passing in early 2020, and later as a project for my class in Theatre History, I found in my archives personal photos and videos of the creation period. Some of these photos will be found to illustrate the article, while a personal, behind the scenes video of that fruitful time serves as another layer of documenting and remembering this work and its creative process.

I found that every production at the CCP Main Theatre was an effort best made with ample pre-production work and specific, out of the box, avenues of support and opportunity. With Opera we found a driving energy from Gabby's complex and specific vision; an intersection of arts and the mythical nature of our own mortality. fragility and temporality.
Keywords: Opera -- Reviews; Ballet Philippines -- Performances; Barredo, Gabriel